Detection of Cyclospora cayetanensis, Echinococcus multilocularis, Toxocara spp. and microsporidia in fresh produce using molecular methods: - A review - Bartosova, B; Koudela, B; Slana, I (Food and waterborne parasitology, 2021)
The current trend for a healthy lifestyle corresponds with a healthy diet, which is associated with regular and frequent consumption of raw fruit and vegetables. However, consumption of ready-to-eat (RTE) food without heat treatment or sufficient washing may pose a risk to consumers. Among the well-known protozoan parasites associated with RTE food and water are Cryptosporidium spp., Giardia duodenalis and Toxoplasma gondii. These belong among prioritized parasitic pathogens, as they are associated with numerous disease outbreaks in humans all around the world. Nevertheless, other parasitic agents such as Cyclospora cayetanensis, Toxocara cati, Toxocara canis, Echinococcus multilocularis and zoonotic microsporidia should not be neglected. Although these selected parasites belong to phylogenetically diverse groups, they have common characteristics associated with fresh produce and each of them poses a health risk to humans. Ensuring healthy food is produced requires the standartization of laboratory methods for the detection of parasitic agents. This article reviews the molecular methods currently used in laboratories for detection of Cyclospora cayetanensis, Toxocara cati, Toxocara canis, Echinococcus multilocularis and zoonotic microsporidia in fresh produce.
Keywords: PCR; Food safety; Parasite; Vegetables; Fruit